How Does the Method of Evaluations Affect their Use? - González Peña, José Danilo (Revista del CLAD Reforma y Democracia, 2022)
The growing needs of citizens in different aspects of daily life, together with the enormous budgetary restrictions to adequately cover them, force public managers to carry out much more efficient and effective policies. One of the main functions of evaluations is to serve as an input in decision-making to improve public policies and in processes related to government accountability. However, in Latin America, and specifically in Colombia, there is little analysis on the use of information from evaluations of public programs and policies. To make progress in closing this gap, a descriptive study and a multivariate analysis were carried out in Colombia to analyze the potential uses of evaluative information and the incidence of the method used in the different types of use. The analysis used information from 251 evaluations from the education, health, social inclusion, agriculture, transportation and infrastructure, and housing sectors at the national level for the period 2008-2019. The main results of this analysis are: i) most of the evaluations show a potential instrumental use, i.e. their findings and recommendations are intended to be used to make direct and immediate decisions about the evaluated program; ii) 23.5% of the evaluations show a potential conceptual use, i.e. they were designed to provide information for accountability exercises or to improve knowledge about how the analyzed program works or operates; iii) instrumental use has a statistically significant and positive relationship with qualitative methods, public procurement and concomitant evaluation; and iv) conceptual use has a statistically significant and negative relationship with qualitative methods and with the agriculture, transportation and housing sectors.
Keywords: Evaluation; Evaluation Models; Policies Evaluation; Programs Evaluation; Methods; Decisions Making; Colombia